1996
DOI: 10.1007/bf02055102
|View full text |Cite
|
Sign up to set email alerts
|

Apple foliage enhances mating disruption of light-brown apple moth

Abstract: Uptake and release of pheromone and behavioral inhibitor ofEpiphyas postvittanna by apple leaves was tested using field electroantennograms (EAG), trap catches to synthetic lures and virgin females, and chemical analysis. Trap catches in single apple trees (N=3) were monitored for six cycles of six days' duration, using delta traps baited with synthetic pheromone. Polyethylene dispensers (0, 1, 10 per tree) releasing pheromone and inhibitor were present for only the first three days of each cycle. Application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…Pre‐exposure of moths to sex pheromone reduced male moth sexual responsiveness in E. postvittana ,28–31 and the present wind tunnel trials after pre‐exposure corroborated this effect with a new method. This physiological and behavioural response contrasts with P. octo , where results confirm that a more rapid recovery of response took place after pre‐exposure, compared with the other two species.…”
Section: Discussionsupporting
confidence: 76%
“…Pre‐exposure of moths to sex pheromone reduced male moth sexual responsiveness in E. postvittana ,28–31 and the present wind tunnel trials after pre‐exposure corroborated this effect with a new method. This physiological and behavioural response contrasts with P. octo , where results confirm that a more rapid recovery of response took place after pre‐exposure, compared with the other two species.…”
Section: Discussionsupporting
confidence: 76%
“…The behavioural inhibitor is a byproduct of the manufacture of the commercialised product, rather than a deliberate addition. The blend tested in the aerosol formulation was the natural pheromone blend,11 while the polyethylene tubing dispensers released an off‐ratio blend3 that has been commercialised in New Zealand and more recently in Australia. Both dispensers were operated at ca 1.5 m above the soil surface.…”
Section: Methodsmentioning
confidence: 99%
“…Prospects for more sustainable apple production in New Zealand would be enhanced by the more cost‐effective use of sex pheromones for mating disruption of leafrollers. Mating disruption should assist insecticide resistance management1, 2 and leafroller pest management by decreasing dependence on insecticides 3. The release rate of most pheromone dispensers is driven by temperature, with the highest release rate during the middle of the day.…”
Section: Introductionmentioning
confidence: 99%
“…Suckling and Clearwater (1990) demonstrated that a 2-component blend provided better communication disruption than the main compound alone. Mating disruption then was conceived as a strategy to achieve, in combination with a reduced spray program, economically acceptable control in insecticide resistant populations in apple in New Zealand Suckling and Shaw 1995). More recently, efficient population control has been demonstrated in Australian citrus (Mo et al 2006).…”
Section: Mating Disruption In Orchardsmentioning
confidence: 99%